2021
DOI: 10.1177/08295735211001653
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Student Well-Being: Stress and Mental Health during Return-to-School

Abstract: Students have been multiply impacted by the COVID-19 pandemic: threats to their own and their family’s health, the closure of schools, and pivoting to online learning in March 2020, a long summer of physical distancing, and then the challenge of returning to school in fall 2020. As damaging as the physical health effects of a global pandemic are, much has been speculated about the “second wave” of mental health crises, particularly for school-aged children and adolescents. Yet, few studies have asked students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
120
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(143 citation statements)
references
References 31 publications
(34 reference statements)
13
120
0
10
Order By: Relevance
“…During the summer of 2020, older school-age adolescents (15-18 years old) reported increased stress caused by physical distancing during the summer and the anticipated challenge of returning to school during the fall [23]. The increased stress level seems to be a constant result independent of the length of the restrictions.…”
Section: Covid-19 Restrictions' Impact On Adolescent Mental Health Behaviors and Psychological Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…During the summer of 2020, older school-age adolescents (15-18 years old) reported increased stress caused by physical distancing during the summer and the anticipated challenge of returning to school during the fall [23]. The increased stress level seems to be a constant result independent of the length of the restrictions.…”
Section: Covid-19 Restrictions' Impact On Adolescent Mental Health Behaviors and Psychological Functioningmentioning
confidence: 99%
“…Healthcare professionals have predicted, and the first published studies have shown, that the COVID-19 pandemic would cause a substantial negative impact on adolescents' lives in the form of an increased prevalence of post-traumatic stress disorder (PTSD), depression, anxiety, grief-related symptoms, and sleep problems [18][19][20][21][22][23].…”
Section: Covid-19 Restrictions' Impact On Adolescent Mental Health Behaviors and Psychological Functioningmentioning
confidence: 99%
“…In our context, partner school divisions shared that they are still attempting to implement standardized suicide risk assessment protocols remotely but do not know optimal practices for delivery (eg, building rapport and safety in a web-based environment, maintaining connections with vulnerable youth), leading to concerns about the safety and effectiveness of this process for students expressing suicide risk in these challenging times. Given the increased mental health distress some youth may experience during and following situations causing widespread loss or turmoil [22][23][24]-including the COVID-19 pandemic [7][8][9]-continued remote use of suicide risk assessment protocols is likely, and thus guidance on e-delivery is critically needed.…”
Section: Suicide Prevention and The Role Of Schoolsmentioning
confidence: 99%
“…In the context of the COVID-19 pandemic, suicide risk for some youth may be elevated because of social isolation and the associated mental health impacts of the pandemic [7][8][9]. In addition, owing to ongoing school closures or remote learning, many youths may not have in-person contact with the school personnel who play a critical role in identifying risk for suicide and supporting students to seek help.…”
Section: Introductionmentioning
confidence: 99%
“…Once schools reopened, students and teachers were reunited, bringing along with them all their lockdown experiences and emotions (Schwartz et al, 2021). This time was particularly challenging for teachers, who had to deal with the psychological effects of this unprecedented situation aside from the uncertainty of how to restart normal school activities (Ozamiz-Etxebarria et al, 2020).…”
mentioning
confidence: 99%